(untitled) (Annals of Medical Research, 2022)
Aim: In this study, the general characteristics of incidental liver metastasis and the factors affecting survival were investigated. Materials and Methods: In our study, we retrospectively analyzed 216 patients with metastases in the liver at diagnosis. Patients with previously known primary malignancy and liver failure due to chronic viral hepatitis were excluded from the study. Results: The etiological causes of metastatic liver lesions were cancer of unknown primary (CUP) 27.78%, pancreato biliary region tumors ( PBRT) 19.44%, colorectal cancer (CRC) 18.98% and 12.96% gastric cancer, in order of frequency. No significant correlation was found in the concordance analysis between CT and USG in detecting metastases In the survival analysis, higher alanine aminotransferase (AST), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), gamma-glutamyl transpeptidase (GGT), cancer antigen 19-9 (CA 19-9), total bilirubin (TBIL), direct bilirubin (DBIL) levels and lower albumin levels were found to be statistically significant in patients who died compared to aliving patients (p<0.05). Survival is shortened and there is an inverse relationship. Good prognostic factors for overall survival: the age of 65 and below, right hepatic lobe metastasis, solitary hepatic lesion, and maximum tumor diameter is 3 cm below, and colorectal tumors. Also, there was a correlation between the presence of extrahepatic metastasis and CA-125 levels. There is a direct correlation between these increased values and the expected extrahepatic metastasis(p<0.05). Conclusion: Many factors are effective in predicting patient survival and prognosis in incidentally detected metastatic liver lesions. Various scoring systems can be developed with prospective, randomized controlled studies to increase their accuracy.